Iwaszkiewicz’s Venice - Pietrych, Krystyna (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2020)
The article offers an overview of Iwaszkiewicz’s Venice works, starting with his early poems from his first visit in the city on a lagoon, and all the way to a work in his final poetry collection. This overview helps one realise that the writer’s autobiography is the key to all of them. Both poems and prose works followed the writer’s rhythm of existence. The presented images not so much extract the features of the city but rather refer to the author’s age, mood, and mental disposition. Another major factor that shaped the image of Venice in Iwaszkiewicz’s works were the conventional topoi consolidated in culture which build the artistic means of symbolising actual spaces. Iwaszkiewicz’s text, which developed for nearly sixty years is a praise of art understood, per modernist principles, in an absolutist manner.